„TRZECI JĘZYK” W PRZEKŁADZIE: SZCZEGÓLNY PRZYPADEK OBCOŚCI NIEOBCEJ - KOTYŃSKA , KATARZYNA (Studia Ukrainica Posnaniensia, 2021)
The aim of the paper is to discuss the strategies used when translating inserts in the “third language” (L3). I focus on the situation where the “third language” remains fully understandable for the recipient of the source text. I will present the strategies for translating the Ukrainian text with Russian incrustations into Polish against a comparative background of other language triads.